2017
DOI: 10.1039/c7sc03448b
|View full text |Cite
|
Sign up to set email alerts
|

Highly photostable wide-dynamic-range pH sensitive semiconducting polymer dots enabled by dendronizing the near-IR emitters

Abstract: A highly photostable, ultra-bright, biocompatible and NIR emissive semiconducting polymer dot (Pdot) based pH sensor was achieved by dendronizing the squaraine probe molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 78 publications
(76 reference statements)
0
32
0
1
Order By: Relevance
“…Compared with organic dyes and quantum dots, Pdots show higher absorptivity and brightness and better photostability and biocompatibility . The oxygen‐sensitive polymer was synthesized by a Suzuki coupling reaction .…”
Section: Methodsmentioning
confidence: 99%
“…Compared with organic dyes and quantum dots, Pdots show higher absorptivity and brightness and better photostability and biocompatibility . The oxygen‐sensitive polymer was synthesized by a Suzuki coupling reaction .…”
Section: Methodsmentioning
confidence: 99%
“…[61][62][63][64] Our group designed a type of Pb 2+ -sensitive Pdots in which the polymer/dye matrices were encapsulated by polydiacetylenes (PDAs) with 15-crown-3 as the functional groups. [36] Copyright 2017, the Royal Society of Chemistry Pb 2+ , the strain of the PDA structure was perturbed, resulting in the chromatic transition from blue to red. [60] Upon the chelation of [60] Copyright 2015, American Chemical Society.…”
Section: Ion Detectionmentioning
confidence: 99%
“…[36] They found that the incorporation of large steric groups on the polymer sidechains could eliminate the ACQ effect and reduce photobleaching in the aggregated state, leading to higher NIR fluorescence and exceptional pH sensing performance. Chiu's lab designed a series of squaraine-based Pdots conjugated with pH-responsive NIR fluorophores.…”
Section: Ph Sensingmentioning
confidence: 99%
“…Semiconducting polymer nanoparticles (SPNs) have recently shown appealing performances as imaging probes and therapeutic agents owing to their high fluorescence brightness, nonblinking behavior, excellent photostability, and good biocompatibility. Owing to the amplified energy transfer ability of SPNs, some fluorescence resonance energy transfer (FRET)‐based SPNs probe for ratiometric detection of metal ion, biomolecule, as well as intracellular pH value and temperature have been reported. However, most of these systems are based on energy transfer from SPNs to small molecules, which are either susceptible to photobleaching or easy to leach from SPNs.…”
Section: Introductionmentioning
confidence: 99%